Software Support for Podcasting Mobile Lecture Content for Education in Sub-Sahara African Universities - Mugwanya, Raymond (Faculty Science: ICTC4D, 2014)
Podcasting is fast gaining traction in developing regions as a means to augment classroom instruction. Commercial podcasting tools such as Apple’s Leopard Server, Tele-task and OpenEya, despite being successfully used in the developed world (where Internet connections are fast and students have powerful multimedia devices) may not be directly transferable to the developing world due to social, economic, technical, political and cultural differences. Thus, we need to gain an understanding of podcasting in developing world Higher Education Institutions in order to develop appropriate tools. Moreover, past podcasting research shows that there is an acute lack of theoretical models, conceptual frameworks as well as evaluation models. Consequently, this thesis employs User Centered Design techniques to offer guidance for contextual podcasting design. In particular, Participatory Action Research was used to gain a deep knowledge of developing world academics’ work context and needs, identify specific requirements, develop a novel podcasting application (called MLCAT – Mobile Learning Content Authoring Tool) and ensure that they accept and use the technology. The final stage of this research was an eight week prototype evaluation aimed at evaluating MLCAT. The main contributions of this thesis are: the identification of design opportunities for podcasting tools (using Participatory Action Research) to support faculty in developing HEIs; a podcasting information ecology model; an adaptation of podcasting to developing country HEIs and a series of design and methodological contributions relating to the design of podcasting tools and other information systems. Findings suggest that academics and students alike valued the need for a seamless podcast production process – one that does not require expensive and sophisticated infrastructure; the ability to author short podcasts or package them into small chunks; the use of Bluetooth for access and sharing podcasts as well as building on tools already in their possession as opposed to completely new ones. This research is one of the few works that relate to podcasting in developing world Higher Education Institutions. It has implications for the design of podcasting applications through an appreciation of the usefulness of research and practice in Human-Computer Interaction for development and how easily this can be adapted to understand and improve mobile learning development practice.